Role of Tourism in Economic Growth: Empirical Evidence from Pakistan Economy (The Pakistan Development Review, 2007)
Tourism activities are considered to be one of the major sources of economic growth. It can be regarded as a mechanism of generating the employment as well as income in both formal and informal sectors. Tourism supplements the foreign exchange earnings derived from trade in commodities and some times finance the import of capital goods necessary for the growth of manufacturing sectors in the economy. On the other hand rapid economic growth in the developed economies attracts foreign travels (Business travels), which leads to an increase in the foreign reserve of the country. Over the past several decades, international tourism has been gaining importance in many economies of the world. According to the World Tourism Organisation (2002), expenditures by 693 million international tourists traveling in 2001 totaled US $ 462 billion, roughly US $ 1.3 billion per day worldwide. In addition, tourists spending have served as an alternative form of exports, contributing to an ameliorated balance of payments through foreign exchange earnings in many countries. The rapid growth of tourism led to a growth of household incomes and government revenues directly and indirectly by means of multiplier effects, improving balance of payments and provoking tourism-promoted government policies. As a result, the development of tourism has generally been considered a positive contribution to economic growth.